2019
DOI: 10.26434/chemrxiv.10067993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Vitro Blood-Brain-Barrier Permeability and Cytotoxicity of Atorvastatin-Loaded Nanoformulation Against Glioblastoma in 2D and 3D Models

Abstract: Inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase of the family of statins have been suggested as therapeutic options in various tumors. Atorvastatin is a statin with potential to cross the blood-brain-barrier, however, the concentrations necessary for a cytotoxic effect against cancer cells exceeds the concentration achievable via oral administration, which made the development of a novel atorvastatin formulation necessary. We characterized the drug loading and basic physicochemical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The pure polymer excipient was proven to be highly cytocompatible even at extremely high concentration of 100 g/l in NCI-H295R and HepG2 cell lines (cell viability > 95%). In general, POx-based amphiphiles have shown tremendous potential for formulation development [110,[112][113][114][115][116][117]. Utilizing the same amphiphile, i.e., pMeOx-pBuOx-pMeOx, Luxenhofer et al previously reported the ultra-high paclitaxel -loaded formulations with the LC of 50 wt% [118].…”
Section: Mitotane: From Oral To Injectable Potential Advantagesmentioning
confidence: 99%
“…The pure polymer excipient was proven to be highly cytocompatible even at extremely high concentration of 100 g/l in NCI-H295R and HepG2 cell lines (cell viability > 95%). In general, POx-based amphiphiles have shown tremendous potential for formulation development [110,[112][113][114][115][116][117]. Utilizing the same amphiphile, i.e., pMeOx-pBuOx-pMeOx, Luxenhofer et al previously reported the ultra-high paclitaxel -loaded formulations with the LC of 50 wt% [118].…”
Section: Mitotane: From Oral To Injectable Potential Advantagesmentioning
confidence: 99%